ASSESSING ECONOMIC RESILIENCE: EFFECTS OF TRADE DISRUPTIONS ON QATAR’S ECONOMIC STABILITY - Abdulkarem, Hayder Abdulrazaq; Siwach, Manoj (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The study investigates the level of resilience that Qatar experienced to withstand trade disruptions and its effects on economic stability. The analysis uses the dataset from 2007 to 2022 leveraging secondary data. It aims to explore how trade disruptions impact two important indicators of macroeconomic performance, i.e., the trade-to-GDP ratio and the debt-to-GDP ratio. The study uses regression analysis for a simple quantification to describe how these factors have been affecting Qatar’s macroeconomic performance in general terms and specifically on economic openness and fiscal soundness. The results indicate that trade disruptions influenced the trade-to-GDP ratio for this very reason, which manifests the extreme reliance of Qatar on international markets. In addition, the Debt to GDP Ratio analysis also shows how trade disruptions can worsen fiscal vulnerabilities in times of acute economic uncertainty. The conclusion highlights the need for economic diversification and strong fiscal measures to make Qatar more resilient economically. As such, this study aims to offer insights into how small trade-oriented economies like Qatar can manage the negative disruptions in economic stability due to global trade.